Percutaneous pelvis fixation using the camera-augmented C-arm: First successes in ex vivo deployment - Unberath, Mathias; Fotouhi, Javad; Tucker, Emerson; Johnson, Alex; Osgood, Greg; Navab, Nassir (Informatik aktuell, 2018)
Today, percutaneous techniques are widely accepted for treatment of bone fractures in spine and pelvis. These techniques are enabled by modern imaging technology, such as mobile C-arm X-ray machines, and allow for substantial reductions in blood loss, collateral tissue damage, and overall surgery duration [1]. While minimally invasive surgery is beneficial for the patient, it increases the task load for the surgeon.
CRIS-Team Scopus Importer:2023-03-08